KONSTRUKSI REALITA “AKSI DAMAI” DALAM PEMBERITAAN GERAKAN BERNUANSA AGAMA DI METROTV - Karmida, Risa (Jurnal Ilmu Komunikasi AKRAB, 2017)
ABSTRACTThe widespread of religious acts and movement have saturated the space of mass media in the Regional Election 2017 campaign event background. Trigerred by blasphemy suspect of a DKI Jakarta Regional Election?s candidate, ended up with serial demonstration and Islamic praying services on 4 November 2016 and 2 December 2016. Mass media entitled ?peaceful act? the first act, and ?super peaceful act? the second act. The peace depiction had been a very emphasized topic in their coverage. The peace reality media has built can not be taken away from its social and political context that happen to be the real background. Eriyanto (2002: 17) explained that reality do not happen naturally, nor revealed by God, it is shaped and constructed. Media put it in a frame, and the frame it self has certain meaning, give specific sense to the audience, wether it has significant point or not. While Luhmann (2000) asserted there are two realities, the first is the real world, and the second is reality in mass media, this has been called double reality. Mass media certainly has significant role to construct the doble reality in the dissemination of information. This dissemination are operated in a close, autopoietic system that neglected outer influence. MetroTV, one of those media that framed religious act as ?peaceful act? has particular historical and political story, that is negative evaluation from the mass toward news with religious contains pointed to be not pro-Islam. When a media captured in its own fear of negative evaluation, they tend to construct reality to save its face. As result, coverage and analitic agencies will decrease or even fade out.Keyword: News with Religious Contains, Peacefulact, MetroTV News Coverage, Reality of Mass Media, Framing.